2014
DOI: 10.1371/journal.pone.0082179
|View full text |Cite
|
Sign up to set email alerts
|

Regional Ion Channel Gene Expression Heterogeneity and Ventricular Fibrillation Dynamics in Human Hearts

Abstract: RationaleStructural differences between ventricular regions may not be the sole determinant of local ventricular fibrillation (VF) dynamics and molecular remodeling may play a role.ObjectivesTo define regional ion channel expression in myopathic hearts compared to normal hearts, and correlate expression to regional VF dynamics.Methods and ResultsHigh throughput real-time RT-PCR was used to quantify the expression patterns of 84 ion-channel, calcium cycling, connexin and related gene transcripts from sites in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
(59 reference statements)
2
20
0
Order By: Relevance
“…Genetic studies have reported a decreased expression of Ca V ␣2␦ transcripts in patients suffering from atrial (43) and ventricular fibrillation (44). Our current results confirm that mutations in CACNA2D1 could be a contributing factor in cardiac sudden death associated with a short QT interval.…”
Section: Congenital Mutations In the Cardiac L-type Channelsupporting
confidence: 85%
“…Genetic studies have reported a decreased expression of Ca V ␣2␦ transcripts in patients suffering from atrial (43) and ventricular fibrillation (44). Our current results confirm that mutations in CACNA2D1 could be a contributing factor in cardiac sudden death associated with a short QT interval.…”
Section: Congenital Mutations In the Cardiac L-type Channelsupporting
confidence: 85%
“…[27][28][29][30] In addition, some studies have observed changes in the gene expression of K ir 6.1/K ir 6.2, underlying the ATP-sensitive K + current (I KATP ), 31,32 NCX1 33 and K ir 2.1/K ir 2.3, molecular components of I K1 . 34,35 Consistent with these molecular data, I K1 density is larger in LV myocytes from guinea pigs, contributing to the stabilisation of the high-frequency rotors in LV. 36,37 However, other studies in different animal models did not find a significant difference between LV and RV I K1 .…”
Section: Differences In Ion Channel Propertiessupporting
confidence: 65%
“…Additionally, the rescuing effect of exogenous PIP 2 on CO inhibition (Fig. 6) 26 . The elevation expression of Kir2.3 during the myopathic period pronounced the greater effect of CO in APD during the myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…As CO inhibits Kir2.3 current and prolongs APD in myocytes, it may cause slowing down of heart rates [28][29][30] and could be considered as a therapeutic target for AF. Kir2.0 has also previously been identified in mammalian forebrain [31][32][33] , nodes of Ranvier 34 , astrocytes 35 , heart 26,27 and renal epithelial cells 36 , serving important roles in setting membrane potential, modulating AP waveform and buffering extracellular K þ . Increased Hmox1 expression has been found in Alzheimer's disease brains 37,38 and its excessive product CO might cause depolarization and excitement of neuron by inhibition of Kir2.0.…”
Section: Discussionmentioning
confidence: 99%